2015
DOI: 10.1007/s00709-015-0858-6
|View full text |Cite
|
Sign up to set email alerts
|

p24 family proteins: key players in the regulation of trafficking along the secretory pathway

Abstract: p24 family proteins have been known for a long time, but their functions have remained elusive. However, they are emerging as essential regulators of protein trafficking along the secretory pathway, influencing the composition, structure, and function of different organelles in the pathway, especially the ER and the Golgi apparatus. In addition, they appear to modulate the transport of specific cargos, including GPI-anchored proteins, G-protein-coupled receptors, or K/HDEL ligands. As a consequence, they have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 126 publications
3
102
0
3
Order By: Relevance
“…COPI vesicles are involved in the traffic of some transmembrane proteins that constitutively cycle between the ER and the Golgi using the COPII and COPI systems, such as members of the p24 family. p24 proteins constitute a family of type I transmembrane proteins of approximately 24 kDa present on the membranes of the early secretory pathway (Pastor-Cantizano et al , 2016). We have previously shown that the C-terminal cytosolic tail of the Arabidopsis p24δ subfamily proteins has the ability to interact with ARF1 and coatomer subunits through a dilysine motif and with COPII subunits through a diaromatic motif (Contreras et al , 2004a, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…COPI vesicles are involved in the traffic of some transmembrane proteins that constitutively cycle between the ER and the Golgi using the COPII and COPI systems, such as members of the p24 family. p24 proteins constitute a family of type I transmembrane proteins of approximately 24 kDa present on the membranes of the early secretory pathway (Pastor-Cantizano et al , 2016). We have previously shown that the C-terminal cytosolic tail of the Arabidopsis p24δ subfamily proteins has the ability to interact with ARF1 and coatomer subunits through a dilysine motif and with COPII subunits through a diaromatic motif (Contreras et al , 2004a, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…p23/24 proteins are a family of conserved COPII‐ and COPI‐enriched vesicle components that function as cargo receptors for a variety of cargoes. Mammals express 10 family members (termed TMED) that form homo‐ and heterodimers and tetramers to support cargo selection and traffic . GPI‐anchored cargo proteins undergo a series of processing events that remodel both the glycan and lipid moieties of the GPI anchor prior to ER exit.…”
Section: Physiological Regulation Of Traffic At Eresmentioning
confidence: 99%
“…These proteins contain a GOLD (Golgi dynamics) domain, which is a β-strand-rich domain found in several proteins that are involved in Golgi dynamics and intracellular protein trafficking1315. Many TMED proteins have been investigated and reported on in detail1617. TMED7, which negatively regulates TLR4 signaling, was identified as a specific inhibitor of the MyD88-independent TLR4 signaling pathway through its ability to facilitate the disruption of the TRIF/TRAM complex by TAG181920.…”
mentioning
confidence: 99%